Effect of temperature-controlled fermentation on physico-chemical properties and lactic acid bacterial count of durian (Durio zibethinus Murr.) pulp - Wasnin, Ramdiah M.; Abdul Karim, Muhammad Shahrim; Mohd Ghazali, Hasanah (Association of Food Scientists & Technologists (India), 2014)
Effects of controlled-temperature fermentation on several physico-chemical properties, lactic acid bacteria (LAB) counts and aroma of durian pulp were examined by storing fresh durian pulp was mixed with 2 % (w/w) salt and stored at 15 °C, 27 °C and 40 °C for 10 days. Storage at 15 °C did not affect the properties of the pulp much. However, at 27 °C and 40 °C, pH and total soluble solids decreased up to 60 % and 52 %, respectively, with greater losses at 27 °C. Titratable acidity, which increased at 27 °C, was due to lactic and acetic acids formation. Loss of sucrose and increases in glucose were greater at 27 °C. LAB population increased up to Day 3 of storage, and then decreased slightly. Principal component analysis based on aroma examination using a zNoseTM showed better retention of aroma profile at 27 °C. Overall, durian fermented at 27 °C was more acceptable than the one prepared at 40 °C, and it is ready to be consumed between Day 4 and 6.